Efektivitas Layanan Individu dengan Teknik Behavior Chart dalam Meningkatkan Kebiasaan Sholat pada Anak Autis di SLBN Autis Sumut - Viny Syahputri; Ira Suryani (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
This study aims to analyze the effectivenessof individual counseling services using behavior chart techniques in improving prayer habits in autistic children at SLBN Autis Sumut. Autistic children often experience obstacles in praying consistently due to difficulties in communication, focus, and adaptation to routines. This study uses a quantitative approach with a quasi-experimental design without full randomization. The sample consisted of five autistic students with low prayer habits who were selected through purposive sampling. The intervention was delivered through four individual counseling sessions using behavior charts as visual monitoring and behavior reinforcement tools. Data were collected using a prayer habit scale instrument that had been tested for validity and reliability 0.849. The pre-test results showed that all participants were in the low category, while the post-test results showed an increase to the high category. The Wilcoxon Signed Ranks test produced a significance value of 0.041 (p < 0.05), indicating a significant change. This study contributes to the field of special guidance and counseling by confirming the effectiveness of behavior charts in shaping religious behavior in autistic children. These findings are important as a basis for developing visual and behavior-based counseling services in special schools.